Boosting Entrepreneurial Support in Libraries: Introducing ASReview for Reference Librarians. - Gupta, Varun (Journal of Web Librarianship)
Libraries, both public and academic, have become essential centers for fostering innovation and supporting entrepreneurs. Libraries reference services for entrepreneurs involve technology recommendations, assist with navigating library resources, creating instructional guides, referencing literature and other library resources, and sometimes conducting systematic literature reviews. This article reports the use of Active learning for Systematic Reviews (ASReview) for strengthening the entrepreneurial support services by adoption of this Artificial Intelligence (AI) technology. A recent consulting project highlighted ASReview's effectiveness in offering support for the entrepreneurs by the reference librarian for providing reference to the literature resources.